Thirukkural: pearls of inspiration (Rupa Publications, 2009)
Wriiten by Thiruvalluvar in Tamil teo thousand years ago,Thirukkural and it's Peals of Wisdom,is as relevant to-day as it was when written.Hence it is known as a book for all ages. The Tirukkural is a classic Tamil sangam literature consisting of 1330 couplets or Kurals.It was authored by Thiruvalluvar. The Tirukku a is one of the most important works in the Tamil language. This is reflected in some of the other names by which the text is given by such as Tami Ma ai (Tamil Veda); Poyy mo i (words that never fail); and Daiva n l (divine text).The work is dated to sometime between the third and first centuries BCE and is considered to precede Manimekalai and Silappatikaram, since they both acknowledge the Kural text